A use-dependent increase in release sites drives facilitation at calretinin-deficient cerebellar parallel-fiber synapses - Brachtendorf, Simone; Eilers, Jens; Schmidt, Hartmut (Frontiers in Cellular Neuroscience, 2015)
Endogenous Ca2+-binding proteins affect synaptic transmitter release and short-term plasticity (STP) by buffering presynaptic Ca2+ signals. At parallel-fiber (PF)-to-Purkinje neuron (PN) synapses in the cerebellar cortex loss of calretinin (CR), the major buffer at PF terminals, results in increased presynaptic Ca2+ transients and an almost doubling of the initial vesicular releases probability (pr). Surprisingly, however, it has been reported that loss of CR from PF synapses does not alter paired-pulse facilitation (PPF), while it affects presynaptic Ca2+ signals as well as pr. Here, we addressed this puzzling observation by analyzing the frequency- and Ca2+-dependence of PPF at unitary PF-to-PN synapses of wild-type (WT) and CR-deficient (CR-/-) mice using paired recordings and computer simulations. Our analysis revealed that PPF in CR-/- is indeed smaller than in the WT, to a degree, however, that indicates that rapid vesicle replenishment and recruitment of additional release sites dominate the synaptic efficacy of the second response. These Ca2+-driven processes operate more effectively in the absence of CR, thereby, explaining the preservation of robust PPF in the mutants.